Balraj Sahni : an intimate portrait - Joshi, Puran Chandra, 1907- (Vikas Pub. House, 1974)
Articles and poems on the Indian screen actor and Panjabi litterateur, Balraj Sahni, 1913-1973, written by his close friends and relatives; a memorial volume.